EFL Learners’ Perception in Using Picture Series-Based Storytelling to Develop Reading Comprehension - Zahratul Fikni; Murniati Murniati; Astrid Dwimaulani; Yulia Agustina (Jurnal Ilmiah Profesi Pendidikan, 2026)
In many EFL contexts, students struggle to develop adequate reading comprehension due to limited vocabulary and an over-reliance on teacher-centered instructional methods. This study aims to examine how EFL learners perceive picture series-based storytelling in developing reading comprehension and to identify the contextual difficulties students face when using this strategy. Employing a descriptive qualitative design, empirical data were collected from 16 eighth-grade students at MTs NWDI Loyok through a Likert-scale questionnaire, semi-structured interviews, and participatory classroom observation. The findings reveal that students hold predominantly positive perceptions of the strategy, reporting stronger motivation, greater confidence, and higher engagement when reading is scaffolded by visual and narrative support. However, students also encountered distinct psychological, linguistic, and contextual difficulties, specifically foreign language anxiety when retelling stories, struggles with limited vocabulary, and a loss of concentration due to classroom noise. The study concludes that picture series-based storytelling is a highly useful and motivating strategy for EFL reading comprehension in rural schools, provided that teachers proactively support students with vocabulary preparation and structured classroom management.